Why does Gojek fail to maintain the Top Brand Award? - Maaz Ud Din; Ana Kadarningsih; Nenny Ariani (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2020)
This study aims to understand the factors that cause Gojek to fail to maintain the Top Brand Award status. To answer the research objectives, the study build a conceptual framework with brand images as a mediating variable of service quality, product, promotion, and price on purchasing decisions. The research sample was 100 respondents. Test of research instruments using factor analysis for validity, and Cronbach Alpha for reliability and use multiple linear regression for data analysis. The result of this study found that the failure of Gojek to maintain the status of the Top Brand Award was caused by the company's lack of strengthening the driving variables. The statement is based on the finding that only price having a significant positive effect on brand images, while service quality, product, and promotion are not significant. The result makes the total impact of exogenous variables less optimal in increasing purchasing decisions.